Design and implementation considerations for a pedagogical object oriented operating system : MTech Thesis, Jan 2009 - Chakraborty, Pinaki (2010)
For centuries, experimentation has been at the center of all successful scientific studies. Experimental explorations can offer new perceptions, weed out unproductive approaches and validate theories and practices. Computer Science (CS), as a discipline, has a poor record when it comes to experimental validation. The ratio of theoretical research claims that have not been experimentally verified is notably high in CS. The situation is no different in the field of system software where experimental research has now become a necessity. The thesis in discussion presents an experimental study on operating systems. The thesis first develops a design of a new operating system, called JNUOS, imparting several noble ideas and then provides a commentary on its implementation.